2000
DOI: 10.1007/s001250051539
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibition reduces retinal overexpression of vascular endothelial growth factor and hyperpermeability in experimental diabetes

Abstract: Despite laser photocoagulation therapy, diabetic retinopathy remains a common cause of visual impairment and blindness [1], principally as a consequence of proliferative retinopathy and macular oedema. Although the pathogenesis of these retinal disorders characterized by retinal neovascularization and exudation is incompletely understood, recent evidence has implicated the vascular endothelial growth factor (VEGF), a permeability-inducing and endothelial cell selective angiogenic glycoprotein as a key factor [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(94 citation statements)
references
References 41 publications
2
88
0
4
Order By: Relevance
“…Consequently, also based on in vitro evidence that angiotensin II increases glucose uptake by retinal pericytes [100], induces release of VEGF by retinal endothelial cells [101], and that blockade of the renin-angiotensin system could prevent new vessel growth in a transgenic animal model of retinopathy of prematurity [102], an angiotensin-receptor blocker is undergoing a clinical trial appropriately targeted and powered to test its possible role in the primary and secondary prevention of DR.…”
Section: Treatment Of Hypertension and Diabetic Retinopathymentioning
confidence: 99%
“…Consequently, also based on in vitro evidence that angiotensin II increases glucose uptake by retinal pericytes [100], induces release of VEGF by retinal endothelial cells [101], and that blockade of the renin-angiotensin system could prevent new vessel growth in a transgenic animal model of retinopathy of prematurity [102], an angiotensin-receptor blocker is undergoing a clinical trial appropriately targeted and powered to test its possible role in the primary and secondary prevention of DR.…”
Section: Treatment Of Hypertension and Diabetic Retinopathymentioning
confidence: 99%
“…To date, there are no published investigations in humans on ACE inhibition therapy and VEGF concentrations in the eye. In rats, ACE inhibitor treat- ment reduced the retinal overexpression of VEGF mRNA both in streptozotocin-induced diabetes [21] and in a retinopathy of prematurity model [25]. ACE inhibitors attenuate the formation of angiotensin II and the break-down of bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of VEGF by angiotensin II requires hyperglycaemic [16] or oxidative conditions [17], which are states that accompany diabetes. In streptozotocin-induced diabetic rats it has been shown that ACE-inhibition reduces the increased concentrations of VEGF mRNA in the retina [21].…”
mentioning
confidence: 99%
“…Treatment of spontaneously hypertensive streptozotocin (STZ)-induced diabetic rats with an ACEI or an AT 1 receptor antagonist reduced VEGF and VEGF-R2 expression [5,6]. In addition, ACE inhibition has been shown to reduce retinal VEGF expression in normotensive STZ-induced diabetic rats [7]. These findings suggest that the angiotensin II/AT 1 pathway contributes to increased retinal VEGF expression in diabetes and hypertension and thereby could contribute to increased vascular permeability and neovascularization.…”
mentioning
confidence: 96%